(untitled) (Research, Society and Development, 2021)
Objective: To report an experience of using thoracic paravertebral block as an alternative to obstetric analgesia. Method: Experience report on the performance of an analgesia technique that was used to contribute to obstetric analgesia and natural childbirth of a pregnant woman with indication for cesarean section due to phobia of the pain of natural childbirth. The experience was in a maternity ward of a medium-sized philanthropic hospital, in the countryside, in the state of Rio Grande do Sul. Results: Bilateral paravertebral thoracic block was the analgesic method chosen for not using the neuro-axis as an anatomical substrate and do not produce hemodynamic fluctuation in the patient and consequences in the fetus. After receiving analgesia, the pregnant woman did not experience pain in the first stage of labor. This technique, in this case, allowed the indication of cesarean section due to phobia of labor pain to be reviewed by the obstetric team and the childbirth developed in a natural way. The maternity nursing team is central to the use of this technique, to conduct monitoring and care for the parturient. Conclusion: Obstetric analgesia contributes to the humanization of natural childbirth. It is necessary to encourage this practice, since it alone tends to increase the number of natural births, considering that in the first prenatal consultation, some pregnant women have the desire to perform cesarean delivery for fear of pain.